Surface Roughness and Fiber Angular Orientation Analysis Toward Laminated Composite Crack Propagation - Hilmi Iman Firmansyah; Bayu Pranoto; Chandra Gunawan; Hangga Wicaksono; Muhammad Fakhruddin (Universitas Sebelas Maret, 2021)
In this study, fatigue testing of fiber metal composites was carried out to determine the rate of crack propagation so that the age of the fiber metal composite specimen was known. The independent variable in this research is the angular orientation of the carbon fiber and the surface roughness of the aluminium with the dependent variable response is the bridge crack rate. The manufacture of fiber metal laminates specimens uses the Vacuum Assist Resin Infusion (VARI) method, which uses a vacuum pump as a means to flow the resin from the reservoir to the mold. Fatigue testing is performed using the stress amplitude method. That is, the value of the load when the tensile test is one third of the tensile strength. After the fatigue test was carried out, the results were obtained on specimens with an angular orientation of 0/90° fibers, the crack propagation rate slowed down with a cycle value of 90,000 in specimens with a surface roughness value of 2.128 µm then decreased cycles on specimens with a value of 2.887 µm, namely 11,000 cycles.